Cognitive Behavior Therapy (CBT) Berbasis Online untuk Menurunkan Kecemasan Ibu Hamil - Dewa Ayu Anggi Gharbelasari; Heni Dwi Windarwati; Laily Yuliatun (Journal of Telenursing (JOTING), 2026)
This article aims to identify online Cognitive Behavior Therapy (CBT) to reducing anxiety levels in pregnant women. The method used was a systematic review, identifying articles from four databases: ScienceDirect, ProQuest, EBSCO, and PubMed, covering the period 2016–2021. Article selection was conducted using the PRISMA method based on predetermined inclusion and exclusion criteria, with keywords: perinatal mental health, antenatal anxiety, antenatal stress, antenatal depression, antenatal intervention, and online CBT. The findings suggest that the advancement of digital mental health services enhances accessibility and strengthens self-efficacy among pregnant women in managing psychological conditions. The implementation of Cognitive Behavioral Therapy (CBT) delivered online has been demonstrated to be effective in reducing anxiety, depression, and stress from pregnancy through the postpartum period. Furthermore, this intervention represents a practical approach to addressing the limited availability of professional mental health services.   Keywords: Antenatal Intervention, Online CBT, Perinatal Mental Health